Sewage sludge treatment by membrane anaerobic system (MAS) - Subramaniam, Vissaliny (2010)
The application of Membrane Anaerobic System (MAS) process treating the raw sewage sludge and the overall MAS treatment efficiency were investigated. The MAS consists of a cross-flow Ultra-filtration membrane for solid-liquid separation with operational pressure of 1.5 to 2 bars. An enrichment mixed culture of methanogenic bacteria was developed and acclimatized in the digester for three days when the seed sludge is fed into the 30 L digester. The raw sewage sludge was collected from Indah Water Municipal Treatment Plant at Taman Seri MahkotaKuantan. The digester was mixed semi-continuously for 4 days at two different concentrations of samples. Two concentration ratios of 50% and 100% of the raw sewage were studied. Results showed throughout the study, the removal efficiency of COD was 88.27% to 94.56%. The Nitrate-N removal was 99.44% to 99.77%. While the removal efficiency of Ammonia-N found 31.69% to 44.44%. About 99.99% of turbidity removal was achieved while the total suspended solids removal found 98.72% to 100%. The methane production rate was between 0.234 L/g COD/d to 0.325 L/g COD/d. The membrane anaerobic system, MAS treatment efficiency was greatly affected by solid retention time, hydraulic retention time and organic loading rates. In this study, membrane fouling and polarization at the membrane surface played a significant role in the formation of the strongly attached cake layer limiting membrane permeability.